Removal of temperature drift of zero of piezoelectric accelerometer - Kvasnikov, Volodymyr; Perederko, Anatolij (Technology audit and production reserves, 2019)
The object of research is the dependence of the results of measuring vibrational acceleration by a piezoelectric accelerometer on the influence of ambient temperature. The indicated dependence is a change in the constant level in the measured signal. This is caused by the generation of an additional charge by the piezoelectric element of the accelerometer in the absence of impact on it from the side of the measurement object. The specified additional charge is generated under the influence of changes in the temperature of the medium on the structure of the sensitive element. This leads to an increase in the error of the measurement result. The larger the range of fluctuations in temperature and the rate of change in the temperature of the medium over time, the greater the effect on the measurement results. Since changes in temperature over time compared with the frequency of measured vibrations are much slower processes and their influence on the measurement result is constant in the entire dynamic range of the accelerometer, they represent an additive component of the error in these measurements. During the study, in order to prevent the temperature influence of the medium on the measurement process, methods for its elimination are considered and solutions for improving the piezoelectric accelerometer by introducing a compensation element in its design are proposed. In order to reduce the influence of temperature fluctuations of the medium on the measurement results, a controlled piezoelectric element operating on the inverse piezoelectric effect along the polarization axis is used as a compensation element. The resulting solution is easily implemented from a technical point of view, since the compensation element and the sensitive element are made of the same material and have the same coefficient of thermal expansion. The compensation element is controlled by an automatic regulation system that works on the principle of deviation regulation. Thanks to the method proposed in this work, it is possible to increase the accuracy of measurements performed using piezoelectric accelerometers and to expand their scope in relation to the requirements for the ambient temperature.